2015
DOI: 10.1007/s10815-015-0548-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the correlation of CATSPER single nucleotide polymorphisms (SNPs) with idiopathic asthenospermia

Abstract: These finding will help to further elucidate the role of CATSPER1 in idiopathic asthenospermia pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…A variety of causative factors lead to AS, including environment, heredity, endocrinal factors, varicocele, immunity, medicine, infection, and microelement deficiencies (Gupta et al, ; Shu et al, ). There is still no directed and effective treatment for AS because of its complex and unexplained etiology and mechanism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of causative factors lead to AS, including environment, heredity, endocrinal factors, varicocele, immunity, medicine, infection, and microelement deficiencies (Gupta et al, ; Shu et al, ). There is still no directed and effective treatment for AS because of its complex and unexplained etiology and mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of causative factors lead to AS, including environment, heredity, endocrinal factors, varicocele, immunity, medicine, infection, and microelement deficiencies (Gupta et al, 2011;Shu et al, 2015).…”
mentioning
confidence: 99%
“…Many factors are related to asthenospermia, in which genetic factors are getting more and more attention. Previous studies have shown that the exonal single nucleotide polymorphism (SNP) rs1893316 in cation channel of sperm associated 1 (CATSPER1), tektin-t (R207H) gene polymorphism, prostate and testis 1 (PATE1) variant (A1423G), endothelial nitric oxide synthase (eNOS) (Glu298Asp) gene polymorphism may be associated with asthenozoospermia risk [4–7].…”
Section: Introductionmentioning
confidence: 99%
“…By scanning of current literature only one study about CatSper ion channels in human was found. This study reported a correlation between CatSper1 mutation and idiopathic asthenospermia ( 10 ).…”
Section: Discussionmentioning
confidence: 61%
“…Even by normal sperm parameters the etiology of infertility remains still unclear by more than 50% of the couples wishing to achieve pregnancy and this phenomenon is called idiopathic infertility ( 1 ). Ion channels are one of the new research topics and are considered to have an important role in the etiology of idiopathic infertility ( 10 ). It has been shown that loss of function in the ion channels may impair sperm physiology by causing abnormal capacitation, loss of hyperactivation and impaired acrosome reaction ( 1 ).…”
Section: Discussionmentioning
confidence: 99%